Teorije/teorija diskurza in literarna veda - Koron, Alenka (Primerjalna književnost, 2005)
Theories/Theory of Discourse and Literary Studies: Part 2. The text is the second part of my article on theories/theory of discourse in literary studies.The first part began with a terminological examination from a perspective which considers theories of discourse as a heterogeneous complex of recent theoretical and methodological approaches at an intersection between social sciences and the humanities. What followed was an overview of the most frequent conceptions of discourse within literary studies (those pertaining to linguistics, narratology, Bakhtin, Kristeva, the philosophy of Habermas, and Foucault), and their epistemological and theoretical suppositions. In the second part of the article, I shed light on two literary applications (by Link and Angenot) of contemporary theories of discourse, and offer a brief outline of their Slovene reception.
Keywords: Link, Jürgen; Angenot, Marc; Juvan, Marko; literarna veda; literary science; teorija diskurza